Toxicidad del extracto metanolico de neem por ingestion del caracol manzana pomacea canaliculata - Chapin Viñan, Ronald Antonio (2015)
Increasing rice production is one of the biggest problems in the world. From its solution depends largely security and peace of nations. Rice plantations in Ecuador are affected by the plague of the snail, which has caused damage to extremely high production aspects. This mollusk entered the rice-growing areas of Ecuador and spread so quickly, it has been considered a pest of quarantine of the grass, it can not only found in rice crops if not as cocoa, banana, banana and ornamental . In the province of El Oro, this mollusk produces indiscriminate use of highly toxic pesticides for control, possibly leading to great damage to the environment and humans mainly by their level of residues in the crop. Faced with this problem demanding markets chemical-free products, an alternative would be to supply the market the use of botanical extracts to control the snail and does not affect humans or the environment. The research of botanical extracts to control snail in our help much, currently there are no natural controls for this quarantine pest such as the snail Pomacea canaliculata for and get a free sustainable agriculture and chemicals that affect the health and the environment.